Risk Factors of Central Obesity in Indonesian Men: A Cross-Sectional Data Study of The Indonesia Family Life Survey 5 (IFLS 5) - , Dahlia; Pribadi, Gracia Satyawestri; Martini, Santi; Yi-Li, Chung (Folia Medica Indonesiana, 2022)
Highlights: • Low levels o physical activity are the major risk factor of central obesity among Indonesian men. • There was a relationship between smoking status, smoker type, cigarette type, physical activity, and meat consumption frequency and the incidence of central obesity. Abstract: Obesity is one of the leading health problems in both developed and developing countries. Central obesity can be defined as a condition where excess fat has accumulated in the abdominal area. There are several risk factors that may cause central obesity in men such as smoking habits, physical activity, and dietary habits. This study aimed to analyse the risk factors of central obesity in Indonesian men. This was an analytical observational study using a cross-sectional design. It used secondary data from the Indonesia Family Life Survey (IFLS 5) with a sample size of 4,648 respondents. The variables studied here were smoking status, type of smoker, type of cigarette, physical activity, and meat consumption frequency. Logistic regression analysis was used. The results of this study showed that the mean age of the respondents was 51 years old. There was a relationship between smoking status (p=0.000), type of smoker (p=0.002), type of cigarette (p=0.000), physical activity (p=0.000), and meat consumption frequency (p=0.024) and the incidence of central obesity. The conclusion of the study was that there was a relationship between smoking status, type of smoker, type of cigarette, physical activity, meat consumption frequency, and the incidence of central obesity, all of which were risk factors of central obesity in Indonesian men. A low level of physical activity was the most prominent risk factor associated with central obesity among Indonesian men. From this study, we suggested controlling the risk factors of central obesity by providing education on the dangers of smoking and the importance of physical activity and a balanced nutritional diet.